Neuropeptides and the Microbiota-Gut-Brain Axis - Holzer, Peter (Adv Exp Med Biol, 2014)
Neuropeptides are important mediators both within the nervous system and between neurons and other cell types. Neuropeptides such as substance P, calcitonin gene-related peptide and neuropeptide Y (NPY), vasoactive intestinal polypeptide, somatostatin and corticotropin-releasing factor are also likely to play a role in the bidirectional gut-brain communication. In this capacity they may influence the activity of the gastrointestinal microbiota and its interaction with the gut-brain axis. Current efforts in elucidating the implication of neuropeptides in the microbiota-gut-brain axis address 4 information carriers from the gut to the brain (vagal and spinal afferent neurons; immune mediators such as cytokines; gut hormones; gut microbiota-derived signalling molecules) and 4 information carriers from the central nervous system to the gut (sympathetic efferent neurons; parasympathetic efferent neurons; neuroendocrine factors involving the adrenal medulla; neuroendocrine factors involving the adrenal cortex). Apart from operating as neurotransmitters, many biologically active peptides also function as gut hormones. Given that neuropeptides and gut hormones target the same cell membrane receptors (typically G protein-coupled receptors), the two messenger roles often converge in the same or similar biological implications. This is exemplified by NPY and peptide YY (PYY), two members of the PP-fold peptide family. While PYY is almost exclusively expressed by enteroendocrine cells, NPY is found at all levels of the gut-brain and brain-gut axis. The function of PYY-releasing enteroendocrine cells is directly influenced by short chain fatty acids generated by the intestinal microbiota from indigestible fibre, while NPY may control the impact of the gut microbiota on inflammatory processes, pain, brain function and behaviour. Although the impact of neuropeptides on the interaction between the gut microbiota and brain awaits to be analysed, biologically active peptides are likely to emerge as neural and endocrine messengers in orchestrating the microbiota-gut-brain axis in health and disease.